2020
DOI: 10.1161/jaha.120.016883
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Pulsatility and Arterial Distensibility Along the Internal Carotid Artery

Abstract: Background Attenuation of velocity pulsatility along the internal carotid artery (ICA) is deemed necessary to protect the microvasculature of the brain. The role of the carotid siphon within the whole ICA trajectory in pulsatility attenuation is still poorly understood. This study aims to assess arterial variances in velocity pulsatility and distensibility over the whole ICA trajectory, including effects of age and sex. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
5
19
0
Order By: Relevance
“…This intersubject variation is likely a combined effect of both physiological differences and measurement errors. Taking an average pulse pressure of 40 mmHg for healthy volunteers, the aPI at C7 (where the vessel is not hampered by the bony carotid canal, as is the case for C3) corresponds to an arterial distensibility of 0.50%/mmHg, which corresponds well with values reported for the intracranial arteries (Giannattasio et al, 2008;Studinger et al, 2003;van Tuijl et al, 2020;Warnert et al, 2015). We observed that the measured blood flow rate between the C3 and C7 was largely preserved.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This intersubject variation is likely a combined effect of both physiological differences and measurement errors. Taking an average pulse pressure of 40 mmHg for healthy volunteers, the aPI at C7 (where the vessel is not hampered by the bony carotid canal, as is the case for C3) corresponds to an arterial distensibility of 0.50%/mmHg, which corresponds well with values reported for the intracranial arteries (Giannattasio et al, 2008;Studinger et al, 2003;van Tuijl et al, 2020;Warnert et al, 2015). We observed that the measured blood flow rate between the C3 and C7 was largely preserved.…”
Section: Discussionsupporting
confidence: 85%
“…We observed that the measured blood flow rate between the C3 and C7 was largely preserved. This shows that our proposed software correctly captures the variation in arterial lumen area and blood flow velocity pulsatility that exists along the distal end of the carotid artery (Schubert et al, 2011;van Tuijl et al, 2020). In most cases, the blood flow rate was slightly lower at the C7 level.…”
Section: Discussionmentioning
confidence: 64%
“…We postulate the reason for the lack of association of PVWMH volume with CCA distensibility coefficient is potentially attributable to the special location of CCA and its bifurcation, which may limit distensibility and its measurement because of the carotid bony canal. 43 Finally, PVWMH volume was not associated with cardiac function in our cohort, which is likely a reflection of the healthy status of our middle‐aged population without a known cardiac disease.…”
Section: Discussionmentioning
confidence: 61%
“…People prone to bone formation may form these calcifications more easily. Intracranial calcifications are common and may result in higher pulsatility, which may be detrimental for ‘soft organs’ such as the brain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%